(untitled) (Bangladesh Journal of Agricultural Research, 2009)
An experiment was carried out to study the grain growth pattern of wheat (Triticum aestivum L.) cultivars and to find out association and linear regression of spike weight and grain weight with time. Spike characters indicated that cultivar differences were significant in all the cases with a few exceptions. Linear regression and correlation coefficients revealed that the association between both spike weight and grain weight with time were highly positively significant among the cultivars but their regression coefficients were non- significant. Key Words: Grain growth, correlation, regression, wheat. DOI: 10.3329/bjar.v34i3.3960 Bangladesh J. Agril. Res. 34(3) : 351-359, September 2009